A Thermo Fluid and Thermo Mechanical Modelling of a Microtubular Solid Oxide Fuel Cell Stack for Unmanned Aerial Vehicles. (2nd June 2015) - Hari, Bostjan; Dhir, Aman; Steinberger-Wilckens, Robert
Abstract : This work presents a three-dimensional thermo fluid and thermo mechanical computational analysis of a microtubular solid oxide fuel cell (SOFC) stack as part of a microtubular SOFC generator. The latter powers a lithium-ion battery as a microtubular SOFC hybrid power system to extend the flight endurance of a mini unmanned aerial vehicle.The microtubular SOFC stack and balance of plant components, comprising microtubular SOFC generator, were designed based on computational fluid dynamics (CFD) assumptions. The stack design process has been further upgraded with thermo mechanical finite element analysis (FEA) simulation to capture deformations and stresses in the stack due to thermal expansion of microtubular SOFCs and manifolds. The developed microtubular SOFC stack will be built based on CFD and FEA predictions and tested to determine the suitability of the microtubular SOFC hybrid power system for this application.